Comparison of the efficacy and safety of onabotulinum toxin A and mirabegron for overactive bladder in elderly patients - Karakeci, A.; Keles, A.; Onur, R. (Verduci Publisher, 2024)
OBJECTIVE: This study aimed to investigate the efficacy and tolerability of mirabegron and onabotulinum toxin A (BoNT/A) injections for overactive bladders. The treatment we provided was to patients over the age of 65 years who were not satisfied with the results of anticholinergic monotherapy. PATIENTS AND METHODS: This multicenter retrospective observational study was conducted between March 2017 and December 2021. Thirty patients who were unable to take anticholinergics or mirabegron due to side effects received a total of 100-unit intravesical injections of BoNT/A. Furthermore, 30 patients receiving 50 mg of mirabegron daily were compared. Micturition frequency, urgency of urinary incontinence, pad usage, and nocturia were all evaluated for efficacy. Patients' health-related quality of life and subjective satisfaction ratings were assessed before and six months after treatment using an incontinence-quality-of-life questionnaire. We documented all adverse events for all subjects. RESULTS: There was a statistically significant decrease in the frequency, daily pad usage, and incontinence episodes of both groups. The median (interquartile range) voiding frequency after onabotulinum toxin A treatment was lower than that after mirabegron treatment [9.4 (6.83-10.0) vs. 10.5 (8.37-11.67); p = 0.01]. Incontinence episodes showed similar differences [1.3 (1.17-3.67) vs. 2.53 (2.0-5.67); p = 0.05]. There was no significant difference in nocturia or maximum urine flow rate between the groups before and after treatment. CONCLUSIONS: We determined that mirabegron led to lower urinary retention, hematuria, infection and post-void residual urine volume rates than BoNT/A in the older patient population. In addition, mirabegron treatment had comparable incontinence-quality-of-life scores at six months post-treatment.
Keywords: Overactive bladder; Elderly; Onabotulinum toxin A; Mirabegron